There will be blood: autohaemorrhage behaviour as part of the defence repertoire of an insect - Bateman, Bill; Fleming, P. (Wiley-Blackwell, 2009)
Armoured ground crickets Acanthoplus discoidalis (Bradyporidae) have an arsenalof defence mechanisms in response to attack. Males but not females can stridulatewhen attacked, while both sexes will bite and regurgitate upon provocation. Theywill also autohaemorrhage. Here we have quantified these responses, examininghow individuals of both sexes respond to repeated simulated predatory attackfrom the side (grabbing the legs with forceps) or from above (grabbing the animalby the pronotum). We found different responses depending on the method ofattack. When attack was directed from the side (at the legs) the crickets can bitetheir attacker and males stridulate intensely. About 62% of such attacks elicited anautohaemorrhage response, where the crickets squirt 1322mg of acrid-smellinghaemolymph 4363mm from seams in the connective tissue between thetrochanter and coxa of each leg and from under the pronotum. By contrast,animals attacked from above could not turn and bite their attacker, and stridulationwas also reduced in males. About 86% of such attacks elicited an autohaemorrhageresponse with 1919 mg of haemolymph projecting 1030mmfrom the body. Autohaemorrhaging is an effective form of chemical defenceagainst bearded dragon lizards Pogona vitticeps (Agamidae) and Aca. discoidalishaemolymph applied to Gryllus bimaculatus nymphs (which have no such chemicaldefence) successfully saved them from predation by striped skinks Trachylepispunctatissima (Scincidae).